Pelatihan Pengelolaan Open Journal System (OJS) Menuju Jurnal Terakreditasi pada Editor Jurnal - Jumani Jumani; Akas Pinaringan Sujalu; Lisa Astria Milasari; Findia Findia (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2022)
Scientific journals are one of the means of formal communication in various knowledge and research results by both researchers and academics. The management of scientific journals towards accredited journals requires several strategies to improve, one of which is at the University of 17 August 1945 Samarinda which currently has 11 journals with an existing open journal system (OJS). This service activity aims to find out and implement the journal publishing process through OJS in accordance with journal accreditation requirements and understand electronic journal management standards based on national journal accreditation regulations and international journal rules. The target of this activity is journal editors as journal managers in the campus environment and able to cooperate in improving accredited journals. The method of this service activity is situation analysis and improvement which is then carried out in four stages, namely the planning stage, activity implementation, activity observation (observation) and mentoring stage. The benchmark for the respondents of the training participants was analyzed in the participant's question and answer session with the journal trainer. In addition, the participants' respondents from the increased understanding of the participants became increased due to their curiosity about the journal management process. Therefore, it can be concluded that the mentoring activities and training provided on the management of scientific journals are effective in increasing participants' understanding in terms of managing scientific journals.